Pengaruh E-Trust Dan E-Service Quality Terhadap E-Loyalty Menggunakan Layanan Mobile Banking Bank Syariah Indonesia Dengan Kepuasan Nasabah Sebagai Variabel Intervening : Studi Kasus Mahasiswa FEBI UINSU Tahun 2019 - Isrul Saleh Siregar; Yenni Samri Juliati Nasution; Nurul Inayah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research aims to analyze how E-Trust and E-Service Quality influence E-Loyalty in mobile banking services, as well as the role of customer satisfaction as a variable that mediates the relationship between E-Trust, E-Service Quality, and E-Loyalty. This research was conducted as a case study on FEBI UINSU students in 2019 who used mobile banking services. The research method used was a survey by distributing questionnaires to FEBI UINSU students who had used mobile banking services. The questionnaire contains questions about their perceptions of E-Trust, E-Service Quality, customer satisfaction, and their level of E-Loyalty towards mobile banking services. The collected data is analyzed using relevant statistical techniques, such as regression analysis, path analysis, or other appropriate methods to test the relationship between the variables in this research.